On the propagation waves in the theory of thermoelasticity with microtemperatures. (July 2016) - Chiriţă, Stan; Danescu, Alexandre
Abstract : Highlights: Studied structure of the waves traveling in materials with microtemperatures. The explicit expressions for the seven waves are obtained. Four transverse waves: two elastic undamped in time and two thermal standing waves. Three dilatational damped in time waves that are coupled. The Rayleigh wave problem is solved and the secular equation is obtained. Abstract: The present paper studies the propagation of plane time harmonic waves in an infinite space filled by a thermoelastic material with microtemperatures. It is found that there are seven basic waves traveling with distinct speeds: (a) two transverse elastic waves uncoupled, undamped in time and traveling independently with the speed that is unaffected by the thermal effects; (b) two transverse thermal standing waves decaying exponentially to zero when time tends to infinity and they are unaffected by the elastic deformations; (c) three dilatational waves that are coupled due to the presence of thermal properties of the material. The set of dilatational waves consists of a quasi-elastic longitudinal wave and two quasi-thermal standing waves. The two transverse elastic waves are not subjected to the dispersion, while the other two transverse thermal standing waves and the dilatational waves present the dispersive character. Explicit expressions for all these seven waves are presented. The Rayleigh surface wave propagation problem is addressed and the secular equation is obtained in an explicit form. Numerical computations are performed for a specific model, and the results obtained are depicted graphically.